Chemoresistance in breast cancer: PI3K/Akt pathway inhibitors vs the current chemotherapy - Kaboli, Parham Jabbarzadeh; Imani, Saber; Jomhori, Masume; Ling, King Hwa (e-Century Publishing, 2021)
Breast cancer is the most prevalent type of cancer among women. Several types of drugs, targeting the specific proteins expressed on the breast cancer cell surface (such as receptor tyrosine kinases and immune checkpoint regulators) and proteins involved in cell cycle and motility (including cyclin-dependent kinases, DNA stabilisers, and cytoskeleton modulators) are approved for different subtypes of breast cancer. However, breast cancer also has a poor response to conventional chemotherapy due to intrinsic and acquired resistance, and an Akt fingerprint is detectable in most drug-resistant cases. Overactivation of Akt and its upstream and downstream regulators in resistant breast cancer cells is considered a major potential target for novel anti-cancer therapies, suggesting that Akt signalling acts as a cellular mechanism against chemotherapy. The present review has shown that sustained activation of Akt results in resistance to different types of chemotherapy. Akt signalling plays a cellular defence role against chemotherapy and (1) enhances multi-drug resistance, (2) increases reactive oxygen species at breast tumor microenvironment, (3) enhances anaerobic metabolism, (4) inhibits the tricarboxylic cycle, (5) promotes PD-L1 upregulation, (6) inhibits apoptosis, (7) increases glucose uptake, and more importantly (8) recruits and interconnects the plasma membrane, nucleus, endoplasmic reticulum, and mitochondria to hijack breast cancer cells and rescue these cells from chemotherapy. Therefore, Akt signalling is considered a cellular defence mechanism employed against chemotherapeutic effects. In addition, interfering roles of PI3K/Akt signalling on the current cytotoxic and molecularly targeted therapy as well as immunotherapy of breast cancer are discussed with a clinical approach. Although, alpelisib, a PIK3CA inhibitor, is the only PI3K/Akt pathway inhibitor approved for breast cancer, we also highlight well-evaluated inhibitors of PI3K/Akt signalling based on different subtypes of breast cancer, which are under clinical trials whether as monotherapy or in combination with other types of chemotherapy.